Thermo-Optic Characterization of Silicon Nitride Resonators for Cryogenic Photonic Circuits - Ali W. Elshaari; Iman Esmaeil Zadeh; Klaus D. Jons; Val Zwiller (IEEE Photonics Journal, 2016)
In this paper, we characterize the Thermo-optic properties of silicon nitride ring resonators between 18 and 300 K. The Thermo-optic coefficients of the silicon nitride core and the oxide cladding are measured by studying the temperature dependence of the resonance wavelengths. The resonant modes show low temperature dependence at cryogenic temperatures and higher dependence as the temperature increases. We find the Thermo-optic coefficients of PECVD silicon nitride and silicon oxide to be $2.51 ± 0.08\ \text{E}$ - $5\ \text{K}^{-1}$ and $0.96 ± 0.09\ \text{E}$ - $5\ \text{K}^{-1}$ at room temperature while decreasing by an order of magnitude when cooling to 18 K. To show the effect of variations in the thermo-optic coefficients on device performance, we study the tuning of a fully integrated electrically tunable filter as a function of voltage for different temperatures. The presented results provide new practical guidelines in designing photonic circuits for studying low-temperature optical phenomena.